CONTINUOUS-FLOW EXTRACTION OF BIOCOMPOUNDS IN FIXED BED: INFLUENCE OF SWAPPING FROM DIRICHLET TO DANCKWERTS CONDITION AT INLET IN PHENOMENOLOGICAL MODELS - de Oliveira, Naila Albertina; Rabi, Jose Antonio (Revista Brasileira de Engenharia de Biossistemas, 2021)
Phenomenological models have increasingly become vital to bioprocess engineering. In continuous-flow biocompounds extraction models, diffusion requires an extra boundary condition at exit (usually null Neumann condition) while either Dirichlet or Danckwerts condition can be imposed at inlet. By taking an extant case study and with the help of an in-house lattice-Boltzmann simulator, this work numerically examines prospective effects of interchanging aforesaid inlet conditions. Trial simulations were performed for scenarios ranging from convective-dominant to diffusive-dominant. Extraction yields numerically simulated under each inlet condition were compared with experimental data. Expected shape of extraction yield curves was simulated whenever process parameters were properly provided and differences due to switching inlet conditions became evident only in diffusion-dominant extraction scenarios. At diffusivities of order 10-6 m2 s-1, numerical results suggest that Danckwerts boundary condition should be preferred at bed inlet.